Developing a conceptual model of symptoms and impacts in progressive fibrosing interstitial lung disease to evaluate patient-reported outcome measures - Wijsenbeek-Lourens, Marlies; Molina-Molina, Maria; Chassany, Olivier; Fox, John; Galvin, Liam; Geissler, Klaus; Hammitt, Katherine M.; Kreuter, Michael; Moua, Teng; O'Brien, Emily C.; Slagle, Ashley F.; Krasnow, Anna; et al. (ERJ Open Research, 2022)
Background An understanding of the experience of patients with progressive fibrosing interstitial lung disease (PF-ILD) is needed to select appropriate patient-reported outcome measures (PROMs) to evaluate treatment effect in clinical trials. - Methods A systematic literature review was conducted to develop a preliminary conceptual model of the symptoms experienced by patients with PF-ILD and the impacts the disease has on them. An online survey and consensus meetings were then conducted with 12-14 stakeholders (patients, clinicians, regulatory and payer advisors) to refine the conceptual model and critically appraise how key concepts should be measured by PROMs. PROMs assessed included Living with Idiopathic Pulmonary Fibrosis, Living with Pulmonary Fibrosis, the King's Brief Interstitial Lung Disease questionnaire, Cough and Sputum Assessment Questionnaire, Evaluating Respiratory Symptoms, Leicester Cough Questionnaire, Functional Assessment of Chronic Illness Therapy (Dyspnoea/Fatigue) and St George's Respiratory Questionnaire for Idiopathic Pulmonary Fibrosis. - Results The literature review identified 36 signs/symptoms and 43 impacts directly or indirectly related to pulmonary aspects of PF-ILD. The most relevant symptoms identified by participants included shortness of breath on exertion, fatigue and cough; relevant impacts included effects on physical functioning, activities of daily living and emotional wellbeing. These are presented in a conceptual model. Consensus opinion was that existing PROMs need further modification and validation before use in clinical trials. - Conclusions The conceptual model improves understanding of the symptoms and impacts that living with PF-ILD has on patients’ wellbeing. It can help to inform the choice of PROMs in clinical trials and highlight aspects to assess in the clinical care of patients with PF-ILD. - Tweetable abstract ERSpublications - click to tweetThis conceptual model of symptoms and impacts in progressive fibrosing interstitial lung disease can help guide patient-reported outcome measure selection in clinical trials https://bit.ly/3tReuGi